The Using Effect of Blended Learning on Students’ Persistence and Learning Outcomes - Salma Samputri; Hamidah Suryani (Postgraduate, University of Mataram, 2024)
This study aims to determine how the using effect of blended learning on students’ persistence and learning outcomes. This type of research is experiment. The independent variable is blended learning while the dependent variables are students’ persistence and learning outcomes. The population is all year seven students of SMPN 1 Kalukku Maumuju Regency of West Sulawesi province which is consists of 146 students divided into five study groups. The sampling technique is random sampling technique to get two study groups where one of them was choosen as the control class and the other class as the experimental class. The data collection techniques used instruments and interverential test. Data analysis techniques are descriptive and inverential analysis. Based on the students’ persistence data, the value of tcalculated = 2.391304 > ttable = 1.67303. It was same result with students’ learning ourcomes where and tcalculated = 7.297297 is bigger than ttable = 1.67303 for student learning outcomes. It can be concluded that blended learnig provides more positive results than conventional learning in terms of students’ persistence and learning outcomes.